Orbital Floor Restoration Using the Transnasal Balloon Technique for Inferior Orbital Wall Fracture. Issue 5 (November 2015) - Lim, Nam Kyu; Kang, Dong Hee; Oh, Sang Ah; Gu, Ja Hea
Abstract : Background: Restoring the volume of orbital fracture is a challenge to the surgeons. We combined the transnasal balloon technique and the transorbital approach during orbital floor reconstruction, and compared the outcomes of this technique with those of the conventional transorbital approach. Methods: Patients with unilateral pure orbital floor fracture were divided according to the surgical method: the direct transconjunctival approach (group A, 20 patients, control group) or the combination approach with the transnasal balloon technique (group B, 20 patients, experimental group). The orbital volume ratio (OVR) was measured with the use of computed tomographic scans, and enophthalmos was checked with a Hertel exophthalmometer. Results: The orbital volume ratios in both groups decreased after surgery: it was more effectively decreased in group B (7.88%) than that in group A (1.69%) ( P < 0.05). Conclusions: A combination of transconjunctival exploration and transnasal restoration with balloon support was more effective in restoring the orbital volume than the conventional method.